BANK LENDING DURING THE COVID-19 CRISIS: EVIDENCE FROM SWITZERLAND - Yu. Strilchuk; K. Cherkashyna; I. Krasnova; S. Arzhevitin; T. Semenenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. This paper is devoted to the analysis of the influence of bank lending on the economy in Switzerland during COVID-19 pandemic. Analysis of the main economic indicators (GDP and its components, inflation, monetary supply) before and during corona-crisis proves that the impact of corona-crisis is stronger than that of the 2008—2009 financial crisis. A sharp decline of GDP, exports and imports is underlined. The components of GDP that were most stable over the last 12 years and did not decrease during the 2008—2009 financial crisis, namely «Households Consumption Expenditures» and «Total Consumption Expenditures», had a negative trend in 2020. It outlines the non-economic nature of the crisis. The pandemic period is characterized by growth of inflation and changes of the money supply structure, such as a reduction of deposits in transaction accounts by half. The most vulnerable economic entity was the population, whose solvency decreased significantly. It led to the consumption and transactions reduction. It is underlined that in such conditions bank lending can be used to boost consumption, consumer demand, stimulate economic growth. The authors’ analysis demonstrates that the amounts of credit lines and utilisation were higher in 2020 during ongoing pandemic compared to the previous year. Loans to individuals remain the most significant in banks credit portfolio, its share was 66 % at the end of 2020. At the same time corporate loans grow faster during the crisis, which indicates businesses have higher demand for credit and use it as a crisis management tool. Contrary to the existing opinion on the negative impact of bank lending on inflation, the article proves that the increase of bank lending as part of fiscal and monetary policy measures has a positive impact on economic recovery during and after the crisis. The analysed Swiss experience can be used in Ukrainian realities.